2003
DOI: 10.1021/ja037063c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Benzene Alkylation over Mesoporous Zeolite Single Crystals:  Improving Activity and Selectivity with a New Family of Porous Materials

Abstract: Mesoporous zeolite single-crystal catalysts are shown to be both more active and more selective than conventional zeolite catalysts in the alkylation of benzene with ethene. The superior catalytic properties are ascribed to improved mass transport in the mesoporous zeolite crystals. Thus, mesoporous zeolite single-crystal catalysts combine the high acidity, shape-selectivity, and hydrothermal stability of zeolites with the efficient mass transport that is typically achieved in mesoporous materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
204
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(216 citation statements)
references
References 15 publications
6
204
1
5
Order By: Relevance
“…Mesoporous MFI zeolite single-crystal catalyst was shown to be both more active and more selective than conventional MFI with only micropores during the alkylation of benzene with ethylene [121]. Such superior catalytic performances were explained by improved mass transport through the mesoporous channel inside the zeolite crystal.…”
Section: Alkylation and Acylation Reactionsmentioning
confidence: 99%
“…Mesoporous MFI zeolite single-crystal catalyst was shown to be both more active and more selective than conventional MFI with only micropores during the alkylation of benzene with ethylene [121]. Such superior catalytic performances were explained by improved mass transport through the mesoporous channel inside the zeolite crystal.…”
Section: Alkylation and Acylation Reactionsmentioning
confidence: 99%
“…34 The world-wide demand for ethylbenzene, which is the raw material for styrene production, is roughly 22 Â 10 6 t per year and is almost exclusively produced by this reaction. The alkylation of benzene with ethene over the H-ZSM-5 catalyst constitutes the heart of the Mobil-Badger process, which was first brought on stream in 1980.…”
Section: Alkylation Of Benzene With Ethenementioning
confidence: 99%
“…Christensen et al showed that the zeolite catalyst with the hierarchical pore architecture is significantly more active than the conventional zeolite catalyst under the reaction conditions employed (T = 583 to 643 K; p = 0.25 MPa), which are sufficiently close to the conditions employed in the industrial process (T = 700 K; p = 2 to 5 MPa). 34 Moreover, the selectivity to ethylbenzene increases by 5 to 10% depending on the benzene conversion. The increased activity is ascribed to the improved mass transport in the mesoporous zeolites which is indicated by an increase of the apparent activation energy from 59 to 77 kJ mol À1 .…”
Section: Alkylation Of Benzene With Ethenementioning
confidence: 99%
“…Especially, the MFI type silicalite-1 (Sil-1) zeolite without cations and silanol defects exhibits high hydrophobic property during the adsorption of volatile organic compounds (VOCs) under wet conditions [4,5]. However, the sole presence of micropores (diameter < 20 Å) limits their use which involves diffusion of bulky molecule [6]. Ordered mesoporous silicates with enlarged pore diameters (20-500 Å) have been developed to overcome these difficulties.…”
Section: Introductionmentioning
confidence: 99%